Effect of Educational Intervention on Correction of Misconceptions about Toxoplasmosis among Pregnant Women at a Rural Area - Galal Abd El-Aal, Bahiga; Ashour Safaan, Nahla; Saleh Abd El-Monem, Eman (International Journal of Nursing Research, 2023)
Aim: This study aims to determine the effect of educational intervention on correction of misconceptions about toxoplasmosis among pregnant women at a rural area. Methods: Quasi- experimental with pre- and post-test design. A multistage random selection of two districts in Menoufia Governorate was done. The researcher randomly selected and conducted this study at maternal and child health center in Teta village from Menouf district and El Iraqia rural health unit from El-Shohada district, Menoufia Governorate, Egypt. A simple random sample of 120 pregnant women selected from maternal and child health center and rural health unit. A structured interview questionnaire consisted of three parts. The first part was concerned with sociodemographic characteristics, the second part was concerned with past and current obstetric history, and the third part was concerned with knowledge of pregnant woman about toxoplasmosis. Results: In pre-intervention, 79.2% of pregnant women had poor score of knowledge about toxoplasmosis while most of them had good knowledge after the intervention. Age, education, and occupation were associated with increase in the score of knowledge. Conclusion: The educational intervention was effective in correction of misconceptions about toxoplasmosis among pregnant women. There was high statistically significant improvement in the mean scores of pregnant women’s total knowledge about toxoplasma infection after the intervention compared with pre-intervention scores. There was highly statistical improvement of pregnant women’s knowledge related to toxoplasmosis preventive measures in the post- intervention than pre-intervention. There was positive association between women’s level of knowledge before the intervention and their age, education, and occupation.